2017
DOI: 10.1002/2016jd026290
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variability in fine mineral dust and coarse aerosol mass at remote sites across the United States

Abstract: Understanding the spatial and temporal variability in fine mineral dust (FD, mineral aerosols with diameters less than 2.5 µm) and coarse aerosol mass (CM, mass of aerosols with diameters between 2.5 and 10 µm) is important for accurately characterizing and perhaps mitigating their environmental and climate impacts. The spatial and seasonal variability of ambient FD and CM was characterized at rural and remote sites across the United States for 2011–2014 using concentration and elemental chemistry data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(136 citation statements)
references
References 115 publications
(226 reference statements)
10
125
1
Order By: Relevance
“…Highest soil concentrations and mass fractions were at the southern coastal OLF site. The International Cooperative for Aerosol Prediction (ICAP) multimodel ensemble (Sessions et al, 2015), NAAPS reanalysis (Xian et al, ), and aerosol chemistry filter analysis (Hand et al, ) indicate that these events are due to intrusions of African dust.…”
Section: Results I: Chemical and Optical Properties For Core Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Highest soil concentrations and mass fractions were at the southern coastal OLF site. The International Cooperative for Aerosol Prediction (ICAP) multimodel ensemble (Sessions et al, 2015), NAAPS reanalysis (Xian et al, ), and aerosol chemistry filter analysis (Hand et al, ) indicate that these events are due to intrusions of African dust.…”
Section: Results I: Chemical and Optical Properties For Core Sitesmentioning
confidence: 99%
“…Similarly, SO 4 2− concentrations peaked in the summer months by 0.3, 0.4, 0.6, and 0.4 μg/m 3 relative to the winter months for CTR, OLF, YRK, and UAH, respectively. The soil/dust also increased in the summer with an increase in agricultural activity, biomass burnings, and long‐distance advection of African dust (Hand et al, ; Xian et al, ), driving a dip in the PM 2.5 :PM 10 ratio.…”
Section: Results Ii: Representativeness Intercorrelation and Perspementioning
confidence: 99%
“…Combustion conditions (i.e., flaming through smoldering) also impact smoke emission factors, chemical composition (e.g., organics, black carbon, and potassium, McMeeking et al, 2009;Lee et al, 2010;Levin et al, 2010;Jen et al, 2019], size, and optical properties . Hand et al (2017) showed that fine dust concentrations are high in the southwestern United States in spring and summer due to abundant local dust sources. Hence, fresh smoke in the west, if dominated by wildfires, may be more absorbing (lower SSA) than in the SE.…”
Section: Introductionmentioning
confidence: 99%
“…However, wind erosion continues on the US Great Plains during times of drought and the potential for land management improvements to be undermined by other policies was highlighted by McCauley et al [136] who attributed part of the blame for a severe dust storm in 1977 to new government incentives to cultivate marginal land. Recent work by Hand et al [137] indicates that fine airborne dust loads (PM 2.5 ) in central and northern parts of the US Great Plains have increased over the period 2000-2014.…”
Section: Policy Lessons Failures and Inadvertent Impactsmentioning
confidence: 99%